EFEKTIVITAS MODEL PEMBELAJARAN LINGKARAN KECIL LINGKARAN BESAR TERHADAP HASIL BELAJAR MAN 2 PONTIANAK - Erni Yanti; Junaidi H Matsum; Rum Rosyid (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine the effectiveness of the use of small circle large learning model on student learning outcomes in the basic concepts of economics in class X MAN 2 Pontianak. The results of the calculation data show that the average student learning outcomes of the experimental class are 77.69 and the average learning outcomes of the control class are 75.00. The difference in the post-test average of the two groups was obtained by the value of t count of 2.14, while the t table with the significance level of 5% or 0.05 was in the two-sided test of 2.5% or 0.025 degrees of freedom (dk) = 76 by 1.99, you can say that count> t table (2.14> 1.99), seen from the sig value. obtained a significance value (Sig. 2-tailed) that is equal to 0.035 this means the significance value <0.05 (0.035 <0.05). It is known that there are differences in the experimental class post-test learning outcomes and the control class of the alternative hypothesis (Ha) accepted and hypotheses zero (Ho) is rejected. From the results of the calculation of the effect size the results are 0.49 with the criteria being medium. Keywords: Basic Concepts of Economics, Learning Outcomes,Small Circle Large Circle